WATERMELON MOSAIC VIRUS OF PUMPKIN (Cucurbita maxima) FROM SULAWESI: IDENTIFICATION, TRANSMISSION, AND HOST RANGE - Wakmana, Wasmo; Kontong, M.S.; Teakle, D.S.; Persley, D.M. (Indonesian Agency for Agricultural Research and Development - MOA, 2002)
A mosaic disease of pumpkin (Cucurbita maxima) was spread widely in Sulawesi. Since the virus had not yet been identified, a study was conducted to identify the disease through mechanical inoculation, aphid vector transmission, host range, and electron microscopic test. Crude sap of infected pumpkin leaf samples was rubbed on the cotyledons of healthy pumpkin seedlings for mechanical inoculation. For insect transmission, five infective aphids were infected per seedling. Seedlings of eleven different species were inoculated mechanically for host range test. Clarified sap was examined under the electron microscope. Seeds of two pumpkin fruits from two different infected plants were planted and observed for disease transmission up to one-month old seedlings. The mosaic disease was transmitted mechanically from crude sap of different leaf samples to healthy pumpkin seedlings showing mosaic symptoms. The virus also infected eight cucurbits, i.e., cucumber (Cucumis sativus), green melon (Cucumis melo), orange/rock melon (C. melo), zucchini (Cucurbita pepo), pumpkin (Cucurbita maxima), water melon (Citrulus vulgaris), Bennicosa hispida, and blewah (Cucurbita sp.). AphidsÂ transmitted the disease from one to other pumpkin seedlings. The virus was not transmitted by seed. The mosaic disease of pumpkin at Maros, South Sulawesi, was associated with flexious particles of approximately 750 nm length, possibly a potyvirus, such as water melon mosaic virus rather than papaya ringspot virus or zucchini yellow mosaic virus.